Informe de Pasantía Cámara de Industria y Comercio Colombo Chilena. “Fortalecimiento Comercial a Empresas de Chile y Colombia” (2020)
The completion of the internship was aimed at applying in a workplace the necessary knowledge during the course of International Commerce, the Universidad Antonio Nariño allows its students as an option to obtain the professional title. In the Colombian Chamber, being a binational entity, there was an approach with the entire commercial sector companies and their main representatives in Colombia and Chile. The management was carried out with market studies, business rapprochement meetings, events where several entrepreneurs stood out, among many other activities. These are aimed at positioning, disclosure and empowerment of customers of each of the affiliated companies.